Antihypertensive Prescription Pattern and Associated Medication Costs: A Retrospective Review of Prescriptions in A Tertiary Hospital - Paul, Onah Otor; Kaigama, Aliyu; Abdulmalik, Ahmed (Asian Journal of Pharmaceutical Research and Development, 2019)
Background: Hypertension is the leading cardiovascular disease most associated with high risk of morbidity and mortality. Recent evidence indicate that in low and medium income countries hypertension is a growing healthcare challenge compounding already existing high burden of infectious diseases. The overall goal of treatment is to reduce the risk of associated secondary complications which increases the risk of mortality. The choice of antihypertensive medications vary widely between and within health facilities, however concerns remain whether prescribed drugs affordable as well as optimize treatment outcomes. Aim: The aim of this study is to determine antihypertensive prescription pattern and its impact on affordability of drug treatment Results/Discussions: The results showed that monotherapy with CCBs were the most prescribed drugs accounting for over half of all antihypertensive prescriptions. In addition CCB based combination therapies were found in more than three quarters of all prescriptions. The cost of one month supply of innovator brands was significantly higher than generic versions, which made them far less affordable to majority of patients. The prescription pattern did not significantly adhere to current treatment guidelines for the management of hypertension. This makes the case for improvement in prescription practices that emphasize rational drug therapy that take into cognizance costs, particularly among the poor. Conclusion: Antihypertensive prescription pattern did not largely comply with guidelines and the widespread prescription of innovator drug brands makes medicines largely unaffordable to majority of patients. It is imperative that drug treatment of high blood pressure allow patients to benefit from reduced cost of low priced generic drugs.